Design, analysis and fabrication of desk mount laptop stand with cooler / Anaqi Bunyamin Zulhazmi - Zulhazmi, Anaqi Bunyamin (2022)
Mechanical Engineering students of semester 4 were given a task to create a product that helps in solving everyday problem. An idea to solve a common problem for laptop users is used for this project which are overheating and the lack of workspace. The objective of this project is to design a laptop stand that helps in increasing the cooling performance of the laptop and gives the user more workspace to be utilized. This proposal contains the major steps in manufacturing a product which are doing research, literature review, implementing a concept design to be visualize in a 3D rendering software, and fabrication. By the completion of this proposal, a more in-depth understanding will be gained and improvement in the ability to write a solid proposal for fabricating an engineering design, which will assist the students in the future professional environment of the engineering world.